2015
DOI: 10.1007/s10897-015-9829-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Neurofibromatosis Type 1 on the Health and Wellbeing of Australian Adults

Abstract: The complications of neurofibromatosis type 1 (NF1) are widespread, unpredictable and variable and each person's experience of this disorder is unique. However, few studies have addressed the impact of NF1 from an individual's perspective. This qualitative study aims to identify the ways in which NF1 impacts upon affected Australian adults. Sixty adults with NF1, with a range of disease severity and visibility participated in a semi-structured interview about the ways in which NF1 impacted upon their life and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 53 publications
8
56
2
Order By: Relevance
“…Therefore, perhaps the visible/cosmetic effects of NF1 are not the sole cause of lower self-esteem in this population, but cognitive effects may also play a major role. This finding is in agreement with previous studies reporting that learning and/or attention problems lead to adverse school experiences, resulting in lower self-esteem and damaged self-image in individuals with NF1 (Ablon 2012;Crawford et al 2015). It is important for parents of children with NF1 to know about the high chance for learning problems so that they can seek intervention at an early age.…”
Section: Factors Influencing Self-esteemsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, perhaps the visible/cosmetic effects of NF1 are not the sole cause of lower self-esteem in this population, but cognitive effects may also play a major role. This finding is in agreement with previous studies reporting that learning and/or attention problems lead to adverse school experiences, resulting in lower self-esteem and damaged self-image in individuals with NF1 (Ablon 2012;Crawford et al 2015). It is important for parents of children with NF1 to know about the high chance for learning problems so that they can seek intervention at an early age.…”
Section: Factors Influencing Self-esteemsupporting
confidence: 92%
“…^Wang et al (2012) also found that individuals with neurofibromatosis (including NF1, NF2, and schwannomatosis) were more likely to experience depression and anxiety because of their diagnosis. Learning deficits in adults with NF1 have been shown to cause feelings of low self-esteem (Crawford et al 2015). Additionally, social self-consciousness in women with NF1 has been associated with lower self-esteem (Smith et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Family planning was an important theme, especially for young adults, which is in line with previous research (Crawford et al, 2015). Patients stated that they would want to have children without NF1 and that additional and timely education about genetics and reproduction was needed, although patients could not agree on the age at which this information should be given.…”
Section: Discussionsupporting
confidence: 88%
“…Family planning was an important theme, especially for young adults, which is in line with previous research (Crawford et al, 2015).…”
Section: Activities and Participationsupporting
confidence: 87%
See 1 more Smart Citation